1984
DOI: 10.1111/j.1365-2125.1984.tb02406.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin metabolism and efficacy in postoperative dental pain.

Abstract: 1 Aspirin 1200 mg was compared with placebo in a randomised, double-blind, crossover study in 15 patients with postoperative pain after removal of impacted lower third molars. 2 Over a 5 h investigation period, patients reported significantly less pain (P < 0.01) after treatment with aspirin, than after treatment with placebo. 3 Peak concentrations of aspirin occurred at 15 min after dosage. 4 Significant negative correlations were observed between plasma aspirin esterase activity and both AUC aspirin (r = -0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 12 publications
2
18
1
Order By: Relevance
“…As in our study, other investigations (Windorfer et al, 1974;Gupta & Gupta, 1977) have noted higher aspirin plasma esterase activity in males than in females. A close correlation (r = 0.90) between aspirin plasma esterase activity and aspirin AUC has been reported (Seymour et al, 1984) in patients with post-operative dental pain but the possible sex-dependency of this association was not determined. Interestingly, these authors also demonstrated a close correlation (r = 0.96) between aspirin AUC and analgesic effect suggesting that pain relief in post-operative dental pain is determined by aspirin hydrolysis rate.…”
Section: Discussionmentioning
confidence: 87%
“…As in our study, other investigations (Windorfer et al, 1974;Gupta & Gupta, 1977) have noted higher aspirin plasma esterase activity in males than in females. A close correlation (r = 0.90) between aspirin plasma esterase activity and aspirin AUC has been reported (Seymour et al, 1984) in patients with post-operative dental pain but the possible sex-dependency of this association was not determined. Interestingly, these authors also demonstrated a close correlation (r = 0.96) between aspirin AUC and analgesic effect suggesting that pain relief in post-operative dental pain is determined by aspirin hydrolysis rate.…”
Section: Discussionmentioning
confidence: 87%
“…It has been previously shown that plasma concentrations of acetylsalicylate are also important determinants of aspirin's efficacy in postoperative dental pain. 2 By contrast, the absorption of solid paracetamol tablets is slow with a Tmax of 60 minutes. 13 Thus differences in pharmacokinetics may account for the differences in onset of analgesia observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These include formulation, dose and plasma concentration of acetylsalicylate. [2][3][4][5] The latter appears to be determined by plasma aspirin esterase activity. By contrast, there is limited information on the efficacy of paracetamol in postoperative dental pain.…”
Section: Introductionmentioning
confidence: 99%
“…Ingested aspirin is hydrolyzed in the gut by first pass metabolism, with about 50 -70% reaching systemic circulation (7,8). The circulating pool of aspirin is hydrolyzed with a half-life of ϳ15 to 20 min (9, 10), but contributes to platelet responsiveness because inhibition is distinctly nonlinear where even small amounts of active cyclooxygenase promote platelet function (11).…”
mentioning
confidence: 99%